Cattle are a potential reservoir of bubaline herpesvirus 1 (BuHV1) - Maidana, Silvina Soledad; Delgado, Fernando Oscar; Vagnoni, Lucas Emilio; Mauroy, Axel; Thiry, Etienne; Romera, Sonia Alejandra (2017)
In the present work, controlled experimental infection and transmission studies in domestic cattle (Bos taurus) and water buffaloes (Bubalus bubalis) were carried out to study the in vivo behaviour of bubaline herpesvirus 1 (BuHV1). Two bovine and two buffalo calves were infected with BuHV1 (20287N isolate) by intranasal aerosolisation. Two sentinel cattle did not receive the virus challenge, but were housed with infected buffaloes to evaluate horizontal transmission. All experimentally inoculated animals showed viral infection and respiratory clinical signs. BuHV1 experimentally infected calves showed intermittent viral excretion between 2 days and 18 days postinfection (dpi) with a maximum titre of excretion of 106 TCID50/ml and moderate rhinitis between 2 dpi and 20 dpi. BuHV1 experimentally inoculated buffaloes showed mild respiratory signs, which consisted mainly of serous nasal secretions during the infection period. Sentinel calves showed mucosal specific IgG1 antibodies at seven days postcontact. Viral DNA was detected by PCR and sequencing in both buffaloes and sentinel calves, which could be associated with latency. In conclusion, this study showed the susceptibility of cattle to BuHV1 after both experimental infection and contact with infected buffaloes. These data increase the scarce knowledge on the pathogenesis in natural host and the susceptibility of cattle to BuHV1 experimental infection.